MLH1 and MSH2 mutations in Colombian families with hereditary nonpolyposis colorectal cancer (Lynch syndrome) - Description of four novel mutations (2005)
This study searched for mutations in the MLH1 and MSH2 genes in 23 unrelated Colombian families with suspected hereditary nonpolyposis colorectal cancer (HNPCC). The families were grouped according to the fulfillment of the Amsterdam II criteria or the Bethesda guidelines. We screened all probands by single-strand conformational polymorphism (SSCP) and direct DNA sequencing. Eleven families fulfilled the Amsterdam criteria II and 12 families the Bethesda guidelines. Germline mutations were detected in 11 families, which corresponds to a mutation detection rate of 48%. When only families fulfilling the Amsterdam II criteria were analyzed, the mutation detection rate rose to 82%. Only 8% of the mutation detection rate was found in families following the Bethesda guidelines. Three mutations were shared by two different families, which corresponds to a total of eight different mutations, seven of them found in the MLH1 gene and one in the MSH2 gene. We have identified four mutations that have not been previously reported to the International Collaborative Group of HNPCC. Three of these are pathogenic, a single base substitution (C > T) at codon 640, exon 17, a G deletion at codon 619, exon 16 and in the MLH1 gene and a two-nucleotide deletion (TG) at codon 184, exon 3 in the MSH2. Also, an unclassified variant, a substitution (C > G) at the codon 141, exon 5 of the MLH1, was detected. © Springer 2005.